2015
DOI: 10.1016/j.ijpharm.2014.11.035
|View full text |Cite
|
Sign up to set email alerts
|

In situ perfusion in rodents to explore intestinal drug absorption: Challenges and opportunities

Abstract: The in situ intestinal perfusion technique in rodents is a very important absorption model, not only because of its predictive value, but it is also very suitable to unravel the mechanisms underlying intestinal drug absorption. This literature overview covers a number of specific applications for which the in situ intestinal perfusion set-up can be applied in favor of established in vitro absorption tools, such as the Caco-2 cell model. Qualities including the expression of drug transporters and metabolizing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 124 publications
2
40
0
1
Order By: Relevance
“…Such as the best intestinal absorption of quercitrin, phloridzin, and phloretin was jejunum, and the ileum may be the best absorption intestine segment of quercetin. These results were similar to the result of related literatures, those reported that quercetin, from Hippophaë rhamnoides extracts, has the best absorption effect in the ileum [14], and the best absorption intestinal segments of the phloridzin monomer is the jejunum [30]. These results were possibly related to the pK a of the drug, the degree of dissociation, pH of the intestinal uid, the surface area of intestine mucosa, the thickness of mucous layers, the activities of enzyme, the ow rate of capillary blood, the components of membrane, the resistance of tight junction, and the distribution of e ux transporters and uptake transporters in the different intestinal [31,32].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Such as the best intestinal absorption of quercitrin, phloridzin, and phloretin was jejunum, and the ileum may be the best absorption intestine segment of quercetin. These results were similar to the result of related literatures, those reported that quercetin, from Hippophaë rhamnoides extracts, has the best absorption effect in the ileum [14], and the best absorption intestinal segments of the phloridzin monomer is the jejunum [30]. These results were possibly related to the pK a of the drug, the degree of dissociation, pH of the intestinal uid, the surface area of intestine mucosa, the thickness of mucous layers, the activities of enzyme, the ow rate of capillary blood, the components of membrane, the resistance of tight junction, and the distribution of e ux transporters and uptake transporters in the different intestinal [31,32].…”
Section: Discussionsupporting
confidence: 93%
“…And the absorption is one of the most important aspects. Generally, orally administered drugs are absorbed from the gastrointestinal tract, and intestinal permeability is considered to be a key determinant of the absorbed dose fraction, which directly affects bioavailability and bioequivalence, and will guide the design of oral drug products [13,14]. But there were no relative researches on the absorption of the Malus hupehensis (Pamp.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-documented method to explore the performance of drug delivery systems in situ is the intestinal perfusion technique in rodents, introduced by Schanker in 1958 [29]. Several decades later, the technique is still widely applied in the field of intestinal absorption research due to its versatility [30][31][32]. Furthermore, the in situ technique provides the opportunity to investigate absorption and mucoadhesion simultaneously in a specific region of the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some advantages of the well‐established everted gut sac model like similarity to an in vivo situation, a relatively large surface area available for absorption and the presence of a mucus layer, the everted gut sac model is unable to provide quantitative data on the absorption kinetics of detailed parameters, and the intestine tissue is easily damaged because of interruptions to local blood flow and interruption of nerves (Luo et al , ). The disadvantages of the everted gut sac model can be remedied by using an in situ single‐pass intestinal perfusion model, which provides intact intestinal mucosa, nerve system and blood flow, together with expression of enzymes as well as transporters (Stappaerts et al , ). Consequently, the combination of using ex vivo everted intestinal sac and in situ single pass perfusion methods are commonly used.…”
Section: Introductionmentioning
confidence: 99%